2009
DOI: 10.1021/ef900314j
|View full text |Cite
|
Sign up to set email alerts
|

Visual Representation of Carbon Dioxide Adsorption in a Low-Volatile Bituminous Coal Molecular Model

Abstract: Carbon dioxide can be sequestered in unmineable coal seams to aid in mitigating global climate change, while concurrently CH 4 can be desorbed from the coal seam and used as a domestic energy source. In this work, a previously constructed molecular representation was used to simulate several processes that occur during sequestration, such as sorption capacities of CO 2 and CH 4 , CO 2 -induced swelling, contraction because of CH 4 and water loss, and the pore-blocking role of moisture. This is carried out by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…The simulation results matched well with the experimental results. The values for CH 4 varied as 0.04–0.91 mmol/g, whereas 0.68–1.92 mmol/g held for CO 2 . , Narkiewicz and Mathews employed a macromolecular model (C 13781 H 8022 O 140 N 185 S 23 ) to look into the swelling effect induced by CO 2 adsorption and observed that the direction perpendicular to the bedding plane exhibited the highest swelling effect, which was also in line with the experimental results . Van Niekerk and Mathews used the macromolecular model C 1000 H 846 O 69 N 16 S 2 to represent bituminous coal in order to probe the interaction between coal and various adsorbates, and the authors found that the nonbonding interaction dominated the coal swelling .…”
Section: Molecular Models In the Csg Systemsupporting
confidence: 76%
See 2 more Smart Citations
“…The simulation results matched well with the experimental results. The values for CH 4 varied as 0.04–0.91 mmol/g, whereas 0.68–1.92 mmol/g held for CO 2 . , Narkiewicz and Mathews employed a macromolecular model (C 13781 H 8022 O 140 N 185 S 23 ) to look into the swelling effect induced by CO 2 adsorption and observed that the direction perpendicular to the bedding plane exhibited the highest swelling effect, which was also in line with the experimental results . Van Niekerk and Mathews used the macromolecular model C 1000 H 846 O 69 N 16 S 2 to represent bituminous coal in order to probe the interaction between coal and various adsorbates, and the authors found that the nonbonding interaction dominated the coal swelling .…”
Section: Molecular Models In the Csg Systemsupporting
confidence: 76%
“…As C usually occupies 60–95% of the coal matrix depending on the coal rank, O and H always comprise approximately 5% of the total mass of dry and ash-free coal. , The majority of the remainding elements include S and N. To obtain a more realistic coal model, these heteroatoms are doped on the graphene surface. ,, According to previous reviews, the minor elements in coal are Si, Al, Ca, Mg, K, Na, Fe, Mn, and Ti, as well as halogens including F, Cl, Br, and I, and the trace elements are B, As, Cd, Hg, Mo, and P. In some models, these elements are included for a more accurate prediction . Liu et al.…”
Section: Molecular Models In the Csg Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…MD was another efficient method to reproduce the swelling behaviors of gaseous adsorbates into coal. Narkiewicz and Mathews (2009) calculated the CO 2 -induced swelling of coal via MD and proposed that the anisotropic swelling was greater perpendicular to the bedding plane. The deformation of coal induced by CH 4 adsorption was also quantified via the quenched solid density functional theory (QSDFT) and clarified the adsorption-induced deformation effect (Yang et al, 2010).…”
Section: Gas-induced Coal Swelling and Shrinkagementioning
confidence: 99%
“…MD was another efficient method to reproduce the swelling behaviors of gaseous adsorbates into coal. Narkiewicz and Mathews (2009) calculated the CO 2 -induced swelling of coal via MD and proposed that anisotropic swelling was greater perpendicular to the bedding plane. Based on the poromechanical model, Brochard et al (2011) conducted effective MD work for swelling deformation behaviors of the CS1000 model induced from the adsorption of CO 2 and CH 4 in micropores, clarifying that the differential swelling was independent of the geological temperatures and pressures.…”
Section: Coal Pyrolysis and Gas Generationmentioning
confidence: 99%